口腔病変から診断に至った口腔・皮膚領域の異時性メトトレキサート関連リンパ増殖性疾患の1例 - 石畑, 清秀; 松本, 幸三; 中村, 典史; 村上, 寿理; 野添, 悦郎; 嶋, 香織 (日本口腔外科学会雑誌, 2017)
Methotrexate (MTX) has been recognized as a first-line treatment for rheumatoid arthritis (RA) because of its ability to reduce the proliferation of innate immune cells. Recently, the occurrence of methotrexate-associated lymphoproliferative disorders (MTX-LPD) in the oral cavity has been reported. We describe a case of MTX-LPD associated with asynchronous ulcers in the oral and skin regions that was diagnosed by oral lesions. A 79-year-old man had been receiving MTX for over 7 years as a treatment for RA. Two years earlier, a skin ulcer had developed in the lumbar region, which histopathologically diagnosed as a sarcoma, and he was treated with heavy-ion radiotherapy. Before he presented to our institution, he had severe bilateral gingival pain in the mandibular molar region for 2 months. The oral lesions appeared to be necrotic ulcers, and a pathological examination revealed lymphocytic infiltration involving atypical cells. Based on the patient's medical history and the results of a histopathological reexamination of the skin lesions, both the oral and skin lesions were diagnosed as MTX-LPD. Although the gingival lesions expanded over the next few weeks, the ulcers spontaneously disappeared after MTX treatment was withdrawn. There have been no signs of recurrence for 2 years.